Prolonged family separation is associated with increased risk of mental disorders among refugee fathers. (30th September 2020) - Hvidtfeldt, C; Petersen, J H; Norredam, M
Abstract: Background: Refugees resettled in Western countries experience long periods of family separation due to waiting first for asylum, and then for family reunification. This study aimed to examine if family separation is associated with psychiatric disease among refugee fathers. Methods: We traversed full-population Danish administrative data since 1986 to establish a cohort of refugee fathers from nuclear families in which the father was the first to arrive and resettled alone during 1995-2015, and where the mother and children were later family reunified. We followed these fathers for up to 24 years from the day their residence permit was issued until their first psychiatric diagnosis, emigration, death, or study end, whichever came first. Using Cox proportional hazard regression, we estimated the temporary and longer-term risks of psychiatric disorders for i) the total family separation period, and ii) the family separation decomposed into time waiting for, respectively, asylum and family reunification. Results: 6176 fathers were included in the study. The HR assessing the temporary risk of psychiatric disorders was 2.23[95% CI: 1.72-2.89] for separated fathers compared with those who were already family reunified. As to the longer-term risk, compared with fathers separated for 0-9 months, the HR of psychiatric disorders was 1.54[1.08-2.21] after +9-12 months of separation, increasing to 1.84[1.29-2.62] after +24 months of separation. The decomposition analysis revealed that +6 months of waiting increased the risk of any psychiatric disorder by approximately 40% for both time waiting for asylum and time waiting for family reunification. Conclusions: Strong evidence supports that fathers waiting for their wives and children face an increased risk of psychiatric disease. Countries receiving refugees should be aware that delayed family reunification can lead to adverse mental health effects. Key messages: Family separation is associated with an increased risk of psychiatric disease among refugee fathers—both while the fathers are separated from their families and after family reunification. The risk of psychiatric disease is more than double among refugee fathers still separated from their family compared with those who have been family reunified.